Brief Report: Subclinical Carotid Artery Atherosclerosis Is Associated With Increased Expression of Peripheral Blood IL-32 Isoforms Among Women Living With HIV. (1st October 2021) - El-Far, Mohamed; Hanna, David B.; Durand, Madeleine; Larouche-Anctil, Etienne; Sylla, Mohamed; Chartrand-Lefebvre, Carl; Cloutier, Guy; Goulet, Jean Philippe; Kassaye, Seble; Karim, Roksana; Kizer, Jorge R.; French, Audrey L.; et al.
Abstract : Background: Persistent inflammation in HIV infection is associated with elevated cardiovascular disease (CVD) risk, even with viral suppression. Identification of novel surrogate biomarkers can enhance CVD risk stratification and suggest novel therapies. We investigated the potential of interleukin 32 (IL-32), a proinflammatory multi-isoform cytokine, as a biomarker for subclinical carotid artery atherosclerosis in virologically suppressed women living with HIV (WLWH). Methods and Results: Nested within the Women's Interagency HIV Study, we conducted a cross-sectional comparison of IL-32 between 399 WLWH and 100 women without HIV, followed by a case–control study of 72 WLWH (36 carotid artery plaque cases vs. 36 age-matched controls without plaque). Plasma IL-32 protein was measured by ELISA, and mRNA of IL-32 isoforms (IL-32α, β, γ, D, ε, and θ) was quantified by reverse transcription polymerase chain reaction from peripheral blood mononuclear cells. Plasma IL-32 protein levels were higher in WLWH compared with women without HIV ( P = 0.02). Among WLWH, although plasma IL-32 levels did not differ significantly between plaque cases and controls, expression of IL-32 isoforms α, β, and ε mRNA was significantly higher in peripheral blood mononuclear cells from cases ( P = 0.01, P = 0.005, and P = 0.018, respectively). Upregulation of IL-32β and IL-32ε among WLWH with carotid artery plaque persisted after adjustment for age, race/ethnicity, smoking, systolic blood pressure, body mass index, and history of hepatitis C virus ( P = 0.04 and P = 0.045); the adjusted association for IL-32α was marginally significant ( P = 0.07). Conclusions: IL-32 isoforms should be studied further as potential CVD biomarkers. This is of particular interest in WLWH by virtue of altered IL-32 levels in this population.